The Meaning of the Hijab in Q.S. Al-Ahzab verse 59 Perspective of Tafsir Al-Misbah - Akramul Huda; Rosdialena (Aslama: Journal of Islamic Studies, 2026)
This study aims to examine the meaning of the hijab in QS. Al-Ahzab verse 59 based on the perspective of Tafsir Al-Misbah by M. Quraish Shihab. This study departs from the diverse views of society regarding the concept of the hijab in Islam which is not only understood as a religious identity and a form of compliance with sharia, but also as a means of maintaining honor, dignity, and protection for women. The study was conducted using a qualitative method through a library research approach, namely by examining QS. Al-Ahzab verse 59, the interpretation contained in Tafsir Al-Misbah, and various relevant literature as supporting sources. The results of the study show that according to Quraish Shihab, the command to wear the hijab in QS. Al-Ahzab verse 59 aims to distinguish faithful women so that they are more easily recognized and protected from various forms of harassment, abuse, or treatment that degrades their dignity. In Tafsir Al-Misbah, the hijab is not only interpreted as a physical covering of the genitals, but also as a symbol of modesty, honor, and self-protection in line with Islamic values. This interpretation emphasizes that the essence of the hijab does not lie in a particular style or form of clothing, but rather in achieving the goals of sharia (maqasid al-syarī‘ah), namely maintaining the honor and dignity of women. Therefore, the interpretation of the hijab in Tafsir Al-Misbah demonstrates a contextual and moderate approach because it is able to integrate normative Islamic values with developing social realities. This study is expected to enrich the treasure trove of Islamic thought while providing a more comprehensive understanding of the concept of the hijab and its relevance in the lives of Muslim women in the modern era.